10.2: Invited Paper: Quantum Dots as a new generation of emitting materials in OLEDs. (4th October 2019) - Wedel, Armin; Kim, Yohan; Heyne, Benjamin; Geßner, André
Abstract : Colloidal quantum dots (QDs)‐based light‐emitting diodes (QD‐LEDs) has been actively researched due to the potential impacts to the display and lighting industry base on the unique properties of QDs itself such as size‐dependent bandgap tuneability, narrow emission spectrum, and low‐cost solution‐based processing. However, the most of promising results in the past used cadmium (Cd) contained II‐VI semiconductor nanocrystals. Therefore, a considerable future task is to substitute Cd‐containing QDs with less toxic materials. InP‐based QDs is a promising material among the III‐V semiconductor nanocrystals and it has been already applied in conventional and inverted QD‐LED structure.